Strategi Integrasi Pengembangan Tenaga Pendidik dan Kependidikan di Era Globalisasi pada SMA Kartika IV-3 Surabaya - Aisyandha, Aisyandha; Rosalawati, Fitria; Fitriya, Lailatul; Hoiro, Rif’a Ummul (Lembaga Yasin AlSys, 2024)
In the era of globalization that continues to develop, an integration strategy for the development of teaching and education staff in the era of globalization at SMA Kartika IV-3 Surabaya is crucial to ensuring the success of the education system at the school. This research aims to collect interview results in the form of articles, by means of observations regarding integration strategies for developing teaching and education staff in the era of globalization. The method used is descriptive qualitative, where the researcher will describe and explain in detail the integration strategy for developing teaching and education staff in the era of globalization. This research applies interview data where this data is taken observationally, and various journal sources that are still related to the research title.